Port marketing as a tool of competitive advantage - Choong, Yuon Yee. (2010)
Since the ports have a new role to play in today‟s environment, it operates under a hyper competition environment. It is because the port is become less complacent as their captive cargo is diminishing and its captive market is no longer a certainty. It shows the eroding of its monopolistic position. With such case, seaport management reviews the necessity to adopt the marketing in order to succeed in the hyper competition environment. It is due to marketing is widely practice among the physical market and it has proven to be succeed in business. Nonetheless, seaport marketing is in the emergent phase and scant literature to support seaport marketing is a tool to create competitive advantage. Thus, a research has been done to bridge the gap.